2012
DOI: 10.1021/jf300193g
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Polyphenols of Postprandial Human Plasma and Low-Density Lipoprotein Modification: The Stomach as a Bioreactor

Abstract: Recent studies dramatically showed that the removal of circulating modified low-density lipoprotein (LDL) results in complete prevention of atherosclerosis. The gastrointestinal tract is constantly exposed to food, some of it containing oxidized compounds. Lipid oxidation in the stomach was demonstrated by ingesting heated red meat in rats. Red wine polyphenols added to the rats' meat diet prevented lipid peroxidation in the stomach and absorption of malondialdehyde (MDA) in rat plasma. In humans, postprandial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 85 publications
4
92
0
1
Order By: Relevance
“…In a simulated gastric compartment (Lorrain et al, 2009) and in the rat stomach (Kanner et al, 2012), heme compounds such as myoglobin or metmyoglobin were found to accelerate further degradation of lipid peroxides, either ingested with the diet or formed in the stomach (Kanner, 2007). The lipid hydroperoxide decomposition products including hydroxyl fatty acids and potentially toxic electrophiles such as the aldehydes and epoxides formed in the stomach can afterwards be incorporated in gastric and intestinal tissues (Kanazawa and Ashida, 1998).…”
Section: Effect Of Heme On the Oxidation Of Polyunsaturated Fatsmentioning
confidence: 99%
“…In a simulated gastric compartment (Lorrain et al, 2009) and in the rat stomach (Kanner et al, 2012), heme compounds such as myoglobin or metmyoglobin were found to accelerate further degradation of lipid peroxides, either ingested with the diet or formed in the stomach (Kanner, 2007). The lipid hydroperoxide decomposition products including hydroxyl fatty acids and potentially toxic electrophiles such as the aldehydes and epoxides formed in the stomach can afterwards be incorporated in gastric and intestinal tissues (Kanazawa and Ashida, 1998).…”
Section: Effect Of Heme On the Oxidation Of Polyunsaturated Fatsmentioning
confidence: 99%
“…These PUFAs are highly prone to lipid oxidation (Zhang et al, 2010). During storage, the double bonds of these PUFAs are attacked by free radicals, which results in the formation of conjugated bonds (Kanner et al, 2012). Hence, measuring the amount of unsaturated fatty acids present in sunfl ower oil can be used as a reference to determine the freshness of the oil (Winne Sia et al, 2014).…”
Section: Iodine Valuementioning
confidence: 99%
“…MDA is the standard biomarker for measurement of lipid peroxidation of cell membrane despite other biomarkers such as 4-hydroxynonenal and isoprostanes. MDA are generated from the peroxidation of fatty acids with three double bonds and more where it is the most abundant active carbonyl generated from lipid peroxidation in foods containing high amounts of unsaturated fats (Kanner et al, 2012). Thus, MDA is a robust biomarker in terms of measuring lipid peroxidation in vivo.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars)mentioning
confidence: 99%
“…En el tracto gastrointestinal superior, los polifenoles, al igual que otros antioxidantes, actuarían reduciendo los hidroperóxidos de los alimentos ingeridos y formando complejos con metales de transición, contribuyendo a contrarrestar el estrés oxidativo postprandial 53 . Precisamente, el consumo de vino tinto con las comidas, un componente tradicional de la DMed, evita la oxidación de ácidos grasos poliinsaturados dietarios, reduciendo la aparición postprandial de lipoperóxidos, malondialdehido (MDA) y LDL oxidadas en el plasma [54][55][56][57] . Adicionalmente, los polifenoles son parcialmente metabolizados por la flora microbiana colónica 58 , generando mediadores bioactivos benéficos para la salud humana.…”
Section: Antioxidantesunclassified